2022
DOI: 10.1093/femsre/fuac036
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to genetic manipulation of Enterococci: Current Approaches and Future Directions

Abstract: Enterococcus faecalis and Enterococcus faecium are Gram-positive commensal gut bacteria that can also cause fatal infections. To study clinically relevant multi-drug resistant E. faecalis and E. faecium strains, methods are needed to overcome physical (thick cell wall) and enzymatic barriers that limit the transfer of foreign DNA and thus prevent facile genetic manipulation. Enzymatic barriers to DNA uptake identified in E. faecalis and E. faecium include type I, II and IV restriction modification systems and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 175 publications
0
2
0
Order By: Relevance
“…19 However, enterococci that are normally considered weak pathogens can cause fatal infections if they have vancomycin resistance. 20 In the current study, no significant difference was found for vancomycin and teicoplanin resistance rates of the isolates of the two species related to relocation.…”
Section: Discussioncontrasting
confidence: 61%
“…19 However, enterococci that are normally considered weak pathogens can cause fatal infections if they have vancomycin resistance. 20 In the current study, no significant difference was found for vancomycin and teicoplanin resistance rates of the isolates of the two species related to relocation.…”
Section: Discussioncontrasting
confidence: 61%
“…Although experiments demonstrate that induction of comK results in transformable events while using plasmid DNA, chromosomal recombination events were very rare (40). Additionally, Enterococci are lagging other Gram-positive pathogens in molecular biology because of restrictions in DNA transfer (41). Enterococci contain elements necessary for natural competence, and it was suggested that they could play an alternative role in host colonization and immune invasion, but there has been no evidence for natural competence (42).…”
Section: Discussionmentioning
confidence: 99%
“…LREfm was 0.1% in 2011 increased to 0.6% in 2022, and LREfs was 0.2% from 2011 increase to 3.4% in 2022 (CHINET data) ( Figure 3 ). Several genes are related to linezolid resistance, but optrA and poxtA , is a growing concern, as it is being increasingly reported in both human and veterinary medicine [ 37 ]. OptrA was primary mechanism in LRE that was first detected in a clinical E. faecalis from China in 2015, and was commonly localized within chromosomes or plasmids and can be transmitted through horizontal gene transfer (HGT) via mobile genetic elements such as transposons, integrative and conjugative elements, and insertion sequences [ 38 , 39 ].…”
Section: Enterococcus Faeciummentioning
confidence: 99%